2020
DOI: 10.1038/s41598-020-63467-w
|View full text |Cite
|
Sign up to set email alerts
|

Identification and molecular characterization of the first complete genome sequence of Human Parechovirus type 15

Abstract: Using a metagenomics approach, we have determined the first full-length genome sequence of a human parechovirus type 15 (HPeV15) strain, isolated from a child with acute flaccid paralysis and co-infected with EV-A71. HPeV15 is a rarely reported type. To date, no full-length genome sequence of HPeV15 is available in the GenBank database, where only limited VP1 sequences of this virus are available. Pairwise comparisons of the complete VP1 nucleotide and deduced amino acid sequences revealed that the study strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 66 publications
(80 reference statements)
1
5
1
Order By: Relevance
“…Overall, 11% (22/200) of the samples tested were positive for HPeV RNA ( Table 1 ). The most affected age group was 2 to < 5 years, thus suggesting that children and infants may be at higher risk of HPeV infection [ 27 , 28 , 43 ]. Age data were missing for 54 AFP cases and were therefore excluded from the analysis of the association between age and HPeV detection.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 11% (22/200) of the samples tested were positive for HPeV RNA ( Table 1 ). The most affected age group was 2 to < 5 years, thus suggesting that children and infants may be at higher risk of HPeV infection [ 27 , 28 , 43 ]. Age data were missing for 54 AFP cases and were therefore excluded from the analysis of the association between age and HPeV detection.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, a putative recombination breakpoint was found in the non-structural coding region 2B. In human parechoviruses, several recombination events have been reported in multiple regions, including the non-structural region; however, hot spots of recombination breakpoint have not been reported [17][18][19][20][21][22][23][24][25]. GC content is related to genomic stability and protection of recombination [26,27].…”
mentioning
confidence: 82%
“…Similar PeV‐1, 3, and 4 are the most prevalent in Asia, with higher diversity from China, India, and Pakistan 27,59‐66 . In Africa, there is a high prevalence of PeV‐A1, 2, and 3, with evidence suggesting the circulation of many genotypes in the region 10,16,25,31,67‐69 …”
Section: Epidemiology and Pathogenesismentioning
confidence: 99%
“…27,[59][60][61][62][63][64][65][66] In Africa, there is a high prevalence of PeV-A1, 2, and 3, with evidence suggesting the circulation of many genotypes in the region. 10,16,25,31,[67][68][69] Moreover, most of what is known about HPeVs comes from pediatric infections. The first report of HPeV infection in adults was in 1986, during an outbreak of AFP in Jamaica that claimed the lives of two women aged 26 and 27 years, linked to PeV-A1 (formerly Echovirus 22).…”
Section: Introductionmentioning
confidence: 99%